Treatment With Nonsteroidal Anti-Inflammatory Drugs Fails To Ameliorate Pathology In Cockatiels Experimentally Infected With Parrot Bornavirus-2 - Escandon P (Dove Medical Press, 2019)
Paulina Escandon,1,2 J Jill Heatley,1,3 Ian Tizard,1,2 Jianhua Guo,1,2 HL Shivaprasad,4 Jeffrey MB Musser1,2 1Schubot Exotic Bird Health Center, College of Veterinary Medicine, Texas A&M University, College Station, TX 77843, USA; 2Department of Veterinary Pathobiology, College of Veterinary Medicine, Texas A&M University, College Station, TX 77843, USA; 3Department of Small Animal Clinical Sciences, College of Veterinary Medicine, Texas A&M University, College Station, TX 77843, USA; 4California Animal Health and Food Safety Laboratory System-Tulare, University of California, Tulare, CA, USACorrespondence: Jeffrey MB MusserDepartment of Veterinary Pathobiology, Texas A&M University, Veterinary Medical Sciences Building, 400 Raymond Stotzer Pkwy #4467, College Station, TX 77843, USATel +1 979 458 9946Fax +1 979 458 0321Email Jmusser@cvm.tamu.eduPurpose: Parrot bornavirus is the etiological agent of Parrot bornavirus syndrome, also referred to and comprising proventricular dilatation disease or PDD, macaw wasting disease, enteric ganglioneuritis and encephalitis, and avian ganglioneuritis. It has been suggested that nonsteroidal anti-inflammatory drugs may be able to ameliorate this disease. Therefore, this study investigated the effects of two commonly used nonsteroidal anti-inflammatory drugs, celecoxib and meloxicam, on cockatiels experimentally inoculated with Parrot bornavirus-2 (PaBV-2).Materials and methods: Twenty-seven cockatiels were randomized into 3 groups of 9 birds, matched with respect to historical PaBV shedding, weight, and sex. The cockatiels were inoculated with cell culture-derived PaBV-2 by the intranasal and intramuscular routes. Beginning at 23 days post-inoculation, birds in each group received oral treatment once daily with placebo, meloxicam (1.0 mg/kg), or celecoxib (10.0 mg/kg).Results: Within 33–79 days post-inoculation, 2 birds died and 6 birds were euthanized based on neurological or gastrointestinal signs consistent with Parrot bornavirus syndrome: 2 birds were euthanized in the placebo group, 1 bird died and 1 bird was euthanized in the meloxicam-treated group, and 1 bird died and 3 birds were euthanized in the celecoxib-treated group. Of these 8 birds, black intestinal contents were found upon necropsy in 2 birds of the meloxicam-treated group and 2 birds of the celecoxib-treated group. At day 173 (±2) post-inoculation, the remaining 19 birds were euthanized. Necropsy and histopathology showed lesions characteristic of Parrot bornavirus syndrome in 23 cockatiels. Histopathologic lesions were present in birds of all 3 groups. There was no statistical difference between the groups nor was there a statistical difference among the 3 treatment groups in the detection of PaBV RNA and PaBV nucleoprotein using RT-PCR and immunohistochemistry, respectively.Conclusion: Meloxicam and celecoxib treatments do not appear to alter the clinical presentation, viral shedding, gross lesions, histopathology, or viral distribution. Treatment with NSAIDs may cause gastrointestinal toxicity in cockatiels experimentally inoculated with PaBV-2.Keywords: meloxicam, celebrex, proventricular dilatation disease, parrot bornavirus syndrome, avian bornavirus